Formalisation of the sofware component ontology specification - Bagušytė, Lina; Lupeikienė, Audronė (Lietuvos matematikos rinkinys, 2005)
This paper is devoted to the development and specification problems of software component ontology. The formalisation of the proposed component ontology is presented, too. The choice of ontology interpretation is motivated. The paper discusses the content of the ontology specification and its development. The mereological theory of software component, one of the constituent parts of a formal component specification, is presented.